The effect of spelt flour on the quality of puff pastry - E. N. Efremova; E. S. Taranova; E. A. Zenina; E. A. Kuznetsova; I. A. Shagay (Новые технологии, 2022)
Croissant is one of the puff pastry products. This product is widely distributed in France. The assortment of croissants is very diverse, but in order to increase the assortment and improve the quality of this product, spelt grain flour has been used in our research. The purpose of the research is to study the effect of spelt flour of the Alcoran variety on the quality of puff pastry. The tasks are to consider the production technology of croissant; to investigate the organoleptic and physical and chemical parameters of croissant; to calculate the economic efficiency of the production of croissant. The methods used are the following: the regulatory framework of the research is the legislation of the Russian Federation on standardization and certification, regulatory documents (GOST, technical specifications). The assessment of organoleptic and physical and chemical parameters has been carried out according to the technical specifications 10.71.11-046-38826547-2016. The results are: trial baking has been conducted in the Volgograd State Agrarian University at the Department of Processing Technologies and Food Safety. Puff yeast dough for Croissant is divided into two main technological processes: kneading yeast dough; lamination of dough. The appearance of the croissant with spelt flour is vague, the color is brown, there is a taste of «nutty flavor», sweeter. The conclusion: when calculating the profitability of croissant production, it has been found that the raw material costs of spelt flour products are 1.6 times higher, which is associated with the cost of spelt grain flour. The calculation of profitability has shown an increase in costs by 2% in the production of croissants with spelt flour. The production of spelt culture refers to organic farming. Healthy natural products lead to an increase in the cost of raw materials, which cannot but affect the cost of further products.